Microfinance and the Global Financial Crisis : A Call for BASEL - Kruiff, David (International Finance Corporation, Washington, DC, 2015)
For many years, microfinance has been the poster child of governments, policymakers, and international organizations with the goal of lifting millions of people out of poverty. The notion that microfinance can pursue and achieve the intertwined goals of development and financial profitability without friction predominated. This dual opportunity, combined with a huge untapped market for financial services at the bottom of the pyramid attracted large amounts of funding from international capital markets, triggering unprecedented levels of growth. Until the global financial crisis, the sustainability of the resulting market growth had not been significantly questioned. As the crisis unfolded during the end of 2007, there seemed to be consensus among microfinance practitioners, analysts, and other industry experts that this crisis will be different. The microfinance industry braced itself for anticipated liquidity crunches, increase in costs of funds, and foreign exchange, as well as a sharp rise in portfolio arrears. This paper will: review recent publications that have drawn conclusions on the effects of the global financial crisis based on empirical data research; draw the conclusion that proper governance and risk management systems are essential and can have avoided many of the problems specific microfinance institutions (MFIs) faced during the financial crisis; and highlight Basel framework sections relevant to MFIs and demonstrate how these can be applied to strengthen MFIs.